Assessment of Task, Activities and Working Materials Used in Non-Formal Training of Solar and Satellite System Installation in Niger State - Kuta, J. I. J.; Yusuf, O. O.; Raymond, E. (Journal of Sustainability and Environmental Management, 2022)
The study was designed to assess the tasks, activities and workings materials in the non-formal training of craft man in solar and satellite systems installation in Niger State of Nigeria. Descriptive survey research method was adopted. The population for the study comprised of 243 trainees and 99 master trainers. For this study, the entire population of the trainee and the master trainers was used; hence, sampling was not carried out. The research instrument used in this study was a structured questionnaire, and it involved the use of a Likert scale. The instrument was validated by experts in the Department of Industrial and Technology Education, Federal University of Technology, Minna. Cronbach Alpha co-efficient was used to determine the internal consistency of the instrument and it yielded reliability coefficient of 0.99. Data were collected through questionnaire with the help of six research assistants. SPSS was used to perform analysis of the data. Mean and standard deviation was used to evaluate research questions, while z test was used to test the hypotheses at 0.05 level of significance. The findings from the hypothesis of the study revealed that that there is no significant difference between the mean responses of trainers and trainee on tasks in non- formal training of solar system installation with a the mean and standard deviation of trainer are 3.55 and 0.70 while the mean and standard deviation of trainee are 3.39 and 0.73 respectively, since the p-value (0.52) is greater than 0.05. The study concluded that the need for training of trainee in the working environment and the participation of master trainers in the structuring of the apprenticeship learning to learn comprehensively. The study recommends that master trainers should be appropriate in planning tasks in non-formal training of trainees in solar system installation. The government should provide working materials for trainers and trainee in non-formal training of solar and satellite system installation.